2019
DOI: 10.1016/j.molmet.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 controls brown fat thermogenesis by deacetylation regulation of pathways upstream of UCP1

Abstract: Objective Brown adipose tissue (BAT) is important for thermoregulation in many mammals. Uncoupling protein 1 (UCP1) is the critical regulator of thermogenesis in BAT. Here we aimed to investigate the deacetylation control of BAT and to investigate a possible functional connection between UCP1 and sirtuin 3 (SIRT3), the master mitochondrial lysine deacetylase. Methods We carried out physiological, molecular, and proteomic analyses of BAT from wild-type and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 64 publications
(83 reference statements)
3
30
0
Order By: Relevance
“…Taken together, our work suggests that ALA-biofortified butter could be an alternative to fish oil in activating brown thermogenesis. Emerging evidence also suggests that sirtuin 3 (SIRT3), a NAD + -dependent deacetylase in mitochondria, is a key modulator for brown thermogenesis [24]. Consistent with this study, the transcriptional levels of Sirt3 and SIRT3 protein expression levels were higher in n3Bu-fed BAT than Bu or Ma-fed BAT ( Figure 4C,D).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Taken together, our work suggests that ALA-biofortified butter could be an alternative to fish oil in activating brown thermogenesis. Emerging evidence also suggests that sirtuin 3 (SIRT3), a NAD + -dependent deacetylase in mitochondria, is a key modulator for brown thermogenesis [24]. Consistent with this study, the transcriptional levels of Sirt3 and SIRT3 protein expression levels were higher in n3Bu-fed BAT than Bu or Ma-fed BAT ( Figure 4C,D).…”
Section: Discussionsupporting
confidence: 86%
“…Conforming to the increased mitochondrial mass, the mitochondrial DNA to genomic DNA ratio (mtDNA/gDNA) was significantly higher in n3Bu-fed BAT compared to Bu-or Ma-fed BAT ( Figure 4B). Emerging evidence also suggests that sirtuin 3 (SIRT3), a NAD + -dependent deacetylase in mitochondria, is a key modulator for brown thermogenesis [24]. Consistent with this study, the transcriptional levels of Sirt3 and SIRT3 protein expression levels were higher in n3Bu-fed BAT than Bu or Ma-fed BAT ( Figure 4C,D).…”
Section: Supplementation With Ala-biofortified Butter Facilitated Mitsupporting
confidence: 86%
“…Previous study showed SIRT3 absence in mice resulted in impaired BAT lipid use, whole body thermoregulation, and respiration in BAT mitochondria without affecting UCP1 expression. Further analysis indicated SIRT3 controlled brown fat thermogenesis by deacetylation regulation of pathways upstream of UCP1 [64].…”
Section: Plos Onementioning
confidence: 99%
“…inflammation and WAT browning, the latter through deacetylation regulation of pathways upstream of UCP1 32,33 . It is noteworthy that opposite regulation directions of the OXPHOS pathway and the sirtuin signaling pathway have been recently reported 34 .…”
Section: Resultsmentioning
confidence: 99%